A STUDY OF THE IMPACT OF TEACHING EFFICIENCY OF TEACHERS WORKING IN GOVERNMENT AND PRIVATE EDUCATIONAL INSTITUTIONS ON THE LEARNING ABILITY OF STUDENTS IN THE CONTEXT OF RAIPUR DISTRICT - Sharma, Akhilesh Kumar; Jha, Pragya (ShodhKosh: Journal of Visual and Performing Arts, 2023)
To study the teaching efficiency of teachers working in government and private educational institutions, students of class 9th have been selected as population in Raipur district and 200 teachers from 10 government and 10 private educational institutions have been randomly selected as sample. Flanders’ observation of class interaction analysis system has been used to measure teaching efficiency. Survey method was used for research analysis and T-value was used for verification of hypotheses. The study found that there is no significant difference in the teaching efficiency of teachers working in government and private educational institutions. 200 students from government educational institutions of Raipur district and 200 students studying in private educational institutions have been selected, which includes both urban and rural students, including both boys and girls.